Bisexual Orientation, Divorce and Islamic Law in Indonesia: Legal Standing and Arguments - Warda Silwana Hikmah; Hasnan Bachtiar; Kukuh Dwi Kurniawan (AHKAM : Jurnal Ilmu Syariah, 2022)
Can the bisexual orientation in a marriage bond be considered a legal argument for formulating a verdict in the Indonesia Islamic courts? Does it have such a specific legal standing mentioned directly within any regulation covering the issue of Islamic private law? In answering both these questions, this article implements a normative-juridical inquiry that examines various rational possibilities in developing arguments of law. This article finds that in handling the case of bisexual orientation, the Indonesian legal system has remained a legal vacuum. Consequently, it seems it might not be a direct legal argument because it has no legal standing. This article argues that there is no single legal instrument has been imposed that explicitly mentions the case of the orientation. However, the judge may implement the analogous of the possibility of "adultery that leads to unresolved conflicts" to make a ratio legis of divorce due to the orientation.   AbstrakApakah orientasi biseksual dalam suatu ikatan perkawinan dapat dijadikan sebagai dalil hukum untuk merumuskan suatu putusan di pengadilan? Apakah ia memiliki kedudukan hukum tertentu yang disebutkan secara langsung dalam peraturan apa pun yang mencakup masalah hukum privat Islam? Dalam menjawab kedua pertanyaan tersebut, artikel ini menerapkan penelitian yuridis-normatif yang mengkaji berbagai kemungkinan rasional dalam mengembangkan argumentasi hukum. Artikel ini menemukan bahwa dalam menangani kasus orientasi biseksual, sistem hukum Indonesia masih mengalami kekosongan hukum. Akibatnya, seolah-olah tidak bisa menjadi argumentasi hukum langsung karena tidak memiliki legal standing. Artikel ini berargumen bahwa tidak ada satu pun instrumen hukum yang diberlakukan yang secara eksplisit menyebutkan kasus orientasi tersebut. Namun demikian, hakim dapat menerapkan analogi kemungkinan “perzinahan yang berujung pada konflik yang tidak terselesaikan” untuk membuat rasio logis perceraian karena orientasinya.